Within-subject time series angular velocity differences between high and low velocity fastballs in college baseball pitchers - Nebel, A.; Schmitt, A.; Giordano, K.; Oliver, G. (Sports Medicine and Health Science, 2025)
Purpose The purpose of the current study is to investigate the within-pitcher differences in time series angular velocities of the pelvis, trunk, shoulder, and elbow for high and low velocity fastballs in college baseball pitchers.